Kecerdasan Eksistensial Terhadap Pemahaman Materi Fiqih Tentang Shalat Jenazah Dengan Praktek Sebagai Variable Moderasi - Alfin Halim (Fakta: Jurnal Pendidikan Agama Islam, 2022)
In the world of education the level of intelligence of students is usually measured by the level of maturity of students' thinking. One of the intelligences that students need is existential intelligence. Existential intelligence is characterized by the ability to think something right. The purpose of this study is to determine the influence and how much influence existential intelligence has on the understanding of fiqh material about corpse prayer in students and to describe whether practice can moderate the influence of existential intelligence on the understanding of fiqh material about corpse prayer in students. This research was designed using a quantitative approach with a correlative type. The free variable (X) is existential intelligence, while the bound variable (Y) is the fiqh material understanding of the corpse prayer and the moderation variable (Z) is the practice. This research used a population type of 18 respondents. Data collection techniques use the questionnaire method, and the documentation method. The data analysis technique is a linear regression test with the help of Statictical Package For Social Science (SPSS) For Windows Version 24.0. The conclusion of the study is that there is an influence of existential intelligence on the understanding of fiqh material about corpse prayer in class VII students of MTs. Nurulhuda. This is evidenced by the sig value of 0.001 being below 0.05. The magnitude of the influence of existential intelligence on the understanding of fiqh material about corpse prayer in class VII students of MTs. Nurulhuda was 73.2%. This corresponds to the value in column R is 0.732. While practice can moderate the influence of existential intelligence on the understanding of fiqh material about corpse prayer in class VII students of MTs. Nurulhuda Pakandangan Barat Sumenep in the 2020/2021 regression, this can be seen from the R2 value in the first regression of 0.536 or 53.6% while after there is a second regression equation the R2 value increases by 0.602 or 60.2%